Carbon Footprint Analysis Of Environmental Management In Slum Areas Of Depok City - Della, Sevia; Kristanto, Gabriel Andari (Asian Journal of Social and Humanities, 2025)
Rapid urban population growth and poor spatial planning often lead to the formation of informal settlements, which are vulnerable to environmental degradation and contribute to greenhouse gas (GHG) emissions. This study estimates CO? emissions from the solid waste, wastewater, and clean water sectors in the slums of Depok City. Data was collected through questionnaires from 137 households and laboratory analysis of wastewater, with calculations based on specific emission factors for each sector. Total annual emissions reached 76.93 tons of CO?, with an average of 0.17 tons per person per year. Solid waste accounts for the largest portion (72.63%), followed by wastewater (21.08%). These findings emphasize the need for improvements in waste and wastewater management to support climate change mitigation efforts in urban informal settlements.